Ersatz Capitalism in Indonesian Automotive Industry during The New Order Era, 1969—1998 - Insan Praditya Anugrah (Universitas Gadjah Mada, 2016)
This paper examines a historical trajectory using Kunio Yoshihara’s concept of ersatz capitalism to analyze the development of Indonesian automotive Industry during New Order Era, 1969-1998. The concept analyzes the fact that the ersatz capitalism structure and ersatz capitalists behavior had caused the failure of Indonesian automotive Industry development to achieve self-reliance. Ersatz Capitalism is characterized by patronage between capitalists and bureaucrats, the capitalists reluctance to invest in research and technological development, foreign capital and foreign technology domination, and the domestic capitalists role that act only as a distributor of the manufactured high-technology products of foreign principals instead of doing research and development, in order to seek immediate high profit return with minimum investment. Through the research, this paper analyzes the role of the ersatz capitalists from the various background such as military, Chinese capitalists, and president families and relatives had supported foreign principal domination In Indonesia. Those capitalists are reluctant to support government programs toward self-reliance industry and choose to strengthen their ties with foreign principals, in order to get immediate profit return without much investment and technological research.